EARLY STUNTING PREVENTION THROUGH FUNCTIONAL BEVERAGES FOR FEMALE ADOLESCENTS AT THE ‘AISYIYAH ORPHANAGE NANGGALO PADANG - Meta Rikandi; Asmeri Lamona; Suci Sintia Dewi (Jurnal Pengabdian Ilmu Kesehatan (JPIK), 2026)
Moringa leaves, dates and sweet corn can be combined into a functional drink product rich in nutrients that can be used to prevent anemia, a cause of stunting that often occurs in adolescent girls in orphanages. care . The high price of animal foods high in iron and limited resources mean that the daily needs of adolescent girls are not met, leading to a very high risk of anemia. The aim of this outreach is to educate adolescent girls about the importance of a clean and healthy lifestyle and importance consume food tall substance iron For lower the incidence of stunting due to anemia, especially in the 'Aisyiyiah environment . The socialization implementation method is carried out in the form of 1) counseling (education) about the concept of anemia and its relationship to stunting and the need for early preventive measures using simple ingredients such as moringa leaves and dates to meet daily nutritional adequacy, 2) direct practice of making functional drinks from moringa leaves, dates and sweet corn. 95% of adolescents daughter state understand about importance prevention of stunting since early as well as know sources food vegetable tall substance iron that can consumed For avoid incident anemia causes of stunting and 86% stated like product drink functional from sweet corn , leaves moringa and dates .